Εφαρμογές της συστημικής θεωρίας στο σχολείο: Η τεχνική της αναπλαισίωσης - Γαλανάκη, Ε. (Τετράδια Ψυχιατρικής, 1997)
In this article, we present ways of applying a well-known systemic technique, reframing and paradox, in the management of problematic situations in the school. The rationale, the utility, and the advantages of this technique are described. We discuss notions such as the many different interpretations of the same behavior, the vicious cycle of the interactions and the circular causality, the cooperative perspective, the therapeutic double bind, the self-fulfilling prophecy, the reframing of relapses, etc. We also present two case studies that illustrate the use of the reframing technique in the school context.